β-Catenin and Smad3 regulate the activity and stability of myocardin-related transcription factor during epithelial–myofibroblast transition - Charbonney, Emmanuel (The American Society for Cell Biology, 2011)
Injury to the adherens junctions (AJs) synergizes with transforming growth factor-β1 (TGFβ) to activate a myogenic program (α-smooth muscle actin [SMA] expression) in the epithelium during epithelial–myofibroblast transition (EMyT). Although this synergy plays a key role in organ fibrosis, the underlying mechanisms have not been fully defined. Because we recently showed that Smad3 inhibits myocardin-related transcription factor (MRTF), the driver of the SMA promoter and many other CC(A/T)-rich GG element (CArG) box–dependent cytoskeletal genes, we asked whether AJ components might affect SMA expression through interfering with Smad3. We demonstrate that E-cadherin down-regulation potentiates, whereas β-catenin knockdown inhibits, SMA expression. Contact injury and TGFβ enhance the binding of β-catenin to Smad3, and this interaction facilitates MRTF signaling by two novel mechanisms. First, it inhibits the Smad3/MRTF association and thereby allows the binding of MRTF to its myogenic partner, serum response factor (SRF). Accordingly, β-catenin down-regulation disrupts the SRF/MRTF complex. Second, β-catenin maintains the stability of MRTF by suppressing the Smad3-mediated recruitment of glycogen synthase kinase-3β to MRTF, an event that otherwise leads to MRTF ubiquitination and degradation and the consequent loss of SRF/MRTF–dependent proteins. Thus β-catenin controls MRTF-dependent transcription and emerges as a critical regulator of an array of cytoskeletal genes, the “CArGome.”